Malignant Melanoma: Beyond the Basics. Issue 2 (August 2016) - Pavri, Sabrina N.; Clune, James; Ariyan, Stephan; Narayan, Deepak
Abstract : Learning Objectives: After reading this article, the participant should be able to: 1. Discuss the initial management of cutaneous malignant melanoma with regard to diagnostic biopsy and currently accepted resection margins. 2. Be familiar with the management options for melanoma in specific situations such as subungual melanoma, auricular melanoma, and melanoma in the pregnant patient. 3. Discuss the differentiating characteristics of desmoplastic melanoma and its treatment options. 4. List the indications for sentinel lymph node biopsy and be aware of the ongoing trials and current literature. 5. Discuss the medical therapies available to patients with metastatic melanoma. Summary: Management of the melanoma patient is a complex and evolving subject. Plastic surgeons should be aware of the recent changes in the field. Excisional biopsy remains the gold standard for diagnosis, although there is no evidence that use of other biopsy types alters survival or recurrence. Wide local excisions should be carried out with margins as recommended by National Comprehensive Cancer Network guidelines according to lesion Breslow depth, with sentinel lymph node biopsy being offered to all medically suitable candidates with intermediate thickness melanomas (1.0 to 4.0 mm), and with sentinel lymph node biopsy being considered for high-risk lesions (ulceration and/or high mitotic figures) with melanomas of 0.75 to 1.0 mm. Melanomas diagnosed during pregnancy can be treated with preoperative lymphoscintigraphy and wide local excision under local anesthesia, with sentinel lymph node biopsy under general anesthesia delayed until after delivery. Management of desmoplastic melanoma is currently controversial with regard to the indications for sentinel lymph node biopsy and the efficacy of postoperative radiation therapy. Subungual and auricular melanoma have evolved from being treated by amputation of the involved appendage to less radical procedures—ear reconstruction is now attempted in the absence of gross invasion into the perichondrium, and subungual melanomas may be treated with wide local excision down to and including the periosteum, with immediate full-thickness skin grafting over bone. Although surgical treatment remains the current gold standard, recent advances in immunotherapy and targeted molecular therapy for metastatic melanoma show great promise for the development of medical therapies for melanoma. Abstract : Related Video Content is Available Online.